2012
DOI: 10.2164/jandrol.111.014639
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D in Human Reproductive Tissues: Cellular Localization in Testis and Epididymis and Surface Distribution in Different Sperm Conditions

Abstract: Mammalian sperm surface antigens are acquired either during spermatogenesis or sperm maturation in the epididymis. These antigens, many of which are hydrolytic enzymes, are actively synthesized and secreted by the resident epithelial cells and adsorbed to the sperm membrane as part of posttesticular sperm modification. In this study, we aimed to investigate the expression of cathepsin-D (CAT-D) in human reproductive tissues and its distribution on the sperm surface in different sperm conditions. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Cathepsin D is detected on the sperm surface in humans and undergoes modification to an active form during capacitation [60], in which process it likely plays an important role in the conversion of proacrosine to acrosin [61]. Cathepsin D concentrations in cauda epididymis fluid also correlate strongly with fertility scores of cattle [62], but cathepsin D concentrations in seminal plasma showed no clear relationship with sperm count and morphology in humans [63].…”
Section: Discussionmentioning
confidence: 98%
“…Cathepsin D is detected on the sperm surface in humans and undergoes modification to an active form during capacitation [60], in which process it likely plays an important role in the conversion of proacrosine to acrosin [61]. Cathepsin D concentrations in cauda epididymis fluid also correlate strongly with fertility scores of cattle [62], but cathepsin D concentrations in seminal plasma showed no clear relationship with sperm count and morphology in humans [63].…”
Section: Discussionmentioning
confidence: 98%
“…3C, 3D) with the band density of about 1.7-2. 7× 10 3 arbitrary units suggesting self-biogenesis of MrCAT-D transcripts by developing germ cells in the testis which was rather different from mouse and human cases reported earlier (Saewu et al, 2012;Asuvapongpatana et al, 2013). The single 212-bp β-actin band, as internal controls, was evenly distributed in all tissues studied confirming an equal amount of RNA loaded in each tissue.…”
Section: Sequence Analysis Of Mrcat-d and Its Phylogenetic Analysismentioning
confidence: 59%
“…For substrate interaction, CAT-D requires hydrophobic amino acid cluster at the cleavage site (P1 and P1 positions) and substrate preference P2 site, whereas, the polar amino acid is of preference at the P2 position (Pimenta et al, 2001). In the reproductive system, we have reported its existence in mammalian male reproductive tissues and its surface localization which is acquired from its adsorption from epididymal fluid as part of sperm maturation process (Asuvapongpatana et al, 2013;Saewu et al, 2012). In a few original works of mammalian reproductions, the unique localization of CAT-D as a cell-or region-specific fashion has been revealed in testis and epididymis (Igdoura, Morales & Hermo, 1995;Hermo & Andonian, 2003), despite the fact that CAT-D is abundantly detected in the lysosomes of all somatic cells (Benes, Vetvicka & Fusek, 2008;Masson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been observed in humans. For example, cathepsin D expression has been observed in human Sertoli cells and Leydig cells and was shown to be anchored to the sperm surface in the postacrosomal region [ 64 ]. Evidence that cathepsin D may exhibit an evolutionarily conserved role in sperm physiology comes from a recent study in which cathepsin D was identified as a seminal plasma protein in carp [ 65 ].…”
Section: Discussionmentioning
confidence: 99%